Docosahexaenoic acid inhibits the proliferation of Kras/TP53 double mutant pancreatic ductal adenocarcinoma cells through modulation of glutathione level and suppression of nucleotide synthesis. - Wei-Chia Hung (PLoS ONE, 2020)
The treatment of cancer cells obtained by blocking cellular metabolism has received a lot of attention recently. Previous studies have demonstrated that Kras mutation-mediated abnormal glucose metabolism would lead to an aberrant cell proliferation in human pancreatic ductal adenocarcinoma (PDAC) cells. Previous literature has suggested that consumption of fish oil is associated with lower risk of pancreatic cancer. In this study, we investigated the anti-cancer effects of docosahexaenoic acid (DHA) in human PDAC cells in vitro and in vivo. Omega-3 polyunsaturated fatty acids (PUFAs) such as DHA and eicosapentaenoic acid (EPA) significantly inhibited the proliferation of human PDAC cells. The actions of DHA were evaluated through an induction of cell cycle arrest at G1 phase and noticed a decreased expression of cyclin A, cyclin E and cyclin B proteins in HPAF-II cells. Moreover, it was found that co-treatment of DHA and gemcitabine (GEM) effectively induced oxidative stress and cell death in HPAF-II cells. Interestingly, DHA leads to an increased oxidative glutathione /reduced glutathione (GSSG/GSH) ratio and induced cell apoptosis in HPAF-II cells. The findings in the study showed that supplementation of GSH or N-Acetyl Cysteine (NAC) could reverse DHA-mediated cell death in HPAF-II cells. Additionally, DHA significantly increased cellular level of cysteine, cellular NADP/NADPH ratio and the expression of cystathionase (CTH) and SLCA11/xCT antiporter proteins in HPAF-II cells. The action of DHA was, in part, associated with the inactivation of STAT3 cascade in HPAF-II cells. Treatment with xCT inhibitors, such as erastin or sulfasalazine (SSZ), inhibited the cell survival ability in DHA-treated HPAF-II cells. DHA also inhibited nucleotide synthesis in HPAF-II cells. It was demonstrated in a mouse-xenograft model that consumption of fish oil significantly inhibited the growth of pancreatic adenocarcinoma and decreased cellular nucleotide level in tumor tissues. Furthermore, fish oil consumption induced an increment of GSSG/GSH ratio, an upregulation of xCT and CTH proteins in tumor tissues. In conclusion, DHA significantly inhibited survival of PDAC cells both in vitro and in vivo through its recently identified novel mode of action, including an increment in the ratio of GSSG/GSH and NADP/NADPH respectively, and promoting reduction in the levels of nucleotide synthesis.